Family Digital Literacy Practices and Children’s Mobile Phone Use - Terras, Melody M.; Ramsay, Judith (Frontiers in Psychology, 2016)
Smart phones are ubiquitous in everyday life and are having a major impact on work, education, social relationships and modes of communication. Children are the fastest growing population of smart phone users, with use often focusing around internet access e.g. 1 in 3 internet users in the UK are under 18 years of age. Despite their widespread use, relatively little is known about the factors that underpin children’s use. The home is a significant ecological context of development and recent research has highlighted the importance of the home environment in promoting and supporting the development of both safe and unsafe online behaviour. Yet the importance of these influences currently remains relatively unrecognised. Therefore, in this paper we present a narrative review of evidence examining parental practices concerning digital communication technologies and applications, with a particular focus on smartphones, and how they relate to the use of technology by their children. Emerging evidence to date indicates that two important factors are at play. Firstly, parental technology use is closely related to that of their child. Secondly, that despite parents frequently-voiced concerns about the nature and extent of their child’s mobile phone use, parents themselves often engage in a number of unsafe internet behaviours and excessive phone use in the home environment. Our review identifies two crucial lines of enquiry that have yet to be comprehensively pursued by researchers in the field: firstly, the adoption of a psychological perspective on children’s emergent behaviours with mobile devices and secondly, the influential role of context. Given parental concerns about the possible negative impact of technologies, parental awareness should be raised about the influence of their behaviour in the context of internet safety along with the adoption of good digital literacy practices. It is anticipated that a comprehensive characterisation of the associated contextual factors influencing smartphone use will serve as a catalyst for debate, discussion and future research.